Comparative Advantage of Turkish Olive Oil in Global Markets: An Empirical Analysis - Abdulmusa Sönmüş; Mehmet Hanifi Aslan (Turkish Journal of Agriculture: Food Science and Technology)
Purpose: This study aims to reveal the comparative advantage of the selected countries in olive oil industry. These selected countries are the main olive oil producers and mainly located in Mediterranean Seacoast. Spain, Italy, Greece and Turkey will be the subject countries in this analysis and compared with each other in terms of their export performance and comparative advantage in olive oil industry globally. Olive oil industry has a volume of around 20 billion Euros every year. Design/methodology/approach: The data for the research was collected from mainly World Bank and trade ministries of subject countries. Revealed Comparative advantage Index (RCA) is used to compare the advantage of these countries in olive oil industry. These indexes found in this analysis will be added to the olive oil RCA indexes of these countries that are found in the previous researches. The obtained data were analyzed through RCA Index formula modeling. Findings:Consuming olive oil is increasing day by day over the world. The research results show that Turkey has comparative advantage in olive industry over Greece. Last few years, Turkey has improved its comparative advantage over Italy. Spain and Italy are the leading countries in olive oil industry in terms of comparative advantage. It has also been found that Turkey has consistently increase its advantage over the last decade. Practical implications: After the comparison of RCA indexes of Spain, Greece, Italy and Turkey, it is found that higher amount of production of olive oil is not enough itself to improve the competitiveness of a country in olive oil market. Branding, packaging and marketing activities that are supported by research and development expenditures are highly important factors for a consistent competitive advantage in olive oil industry. Olive oil consumers are highly motivated on the packaging and label of a product when it comes to olive oil. They usually trust Mediterranean brands comparing to others. Originality/value: The study answers the advantages of selected countries in terms of olive oil performance in global markets. Export performance of olive oil is much likely to improve the competitiveness of a country rather than a country that produces high volume of olive oil. Production itself is not enough to increase competitiveness of a country in olive oil market.